The role of the child and the adolescent in Balzac's Comedie humaine - Sahli, Janet (My University, 2015)
The purpose of th is thesis is to correct the widespread misconception th a t children and adolescents are of small Importance in the world of Balzac's Comedie humaine. My method of procedure was not the traditional one. Instead of making'individual characters the focal point of my study, I culled relevant information from the Com&die humaine and then proceeded to group related concepts. Afterwards I consulted Balzac's private correspondence, the Oeuvres de Jeunesse, the Oeuvres diverses and various editions of his works,as well as lite ra ry and social criticism . The present thesis consists o f an Introduction, eight Chapters and a Conclusion. I t is divided into two parts. Part I is concerned with the child and the adolescent per s e . Part II outlines Balzac's view of th e ir growth and development. Chapter I aims to show that Balzac was not only a pioneer in the history of the French novel, but also a pioneer of the treatment of the child therein. Chapter II studies those characteristics which he considered typical of the child personality. They tend to be clinical rath er than lite ra ry , although there is inevitably some overlap and even co n flic t. Chapter III examines types of children mentioned in the Comddie humaine. Personal considerations motivated Balzac to place most emphasis on the only child, the s p o ilt child and, obliquely, the adopted child who then had minimal Importance in French Law. Nevertheless an appearance is made by all types known a t the time to lite ra tu re , society and the law, although not a ll are dissected.
A Thesis Submitted to the Faculty of A rts, University of the Witwatersrand, Johannesburg, for the Degree of Doctor of Philosophy. Johannesburg, January 1973
Keywords: Balzac, Honoré de, 1799-1850--Comédie humaine; Balzac, Honoré de, 1799-1850--Criticism and interpretation